Interaction of flavour compounds with the seasoning base - Annamalai, Nacchiappan (2023)
Industrial seasonings are flavourless bases mixed with aroma and taste active compounds which maybe formulated using different techniques for different applications, each with variable loading capacity and delivery efficiency. Depending on the macro molecule composition and the type of the base, the flavour compounds are bound in the seasoning base differently affecting the effective flavour release. The focus of this research was on the topical application of seasonings, specifically cheese and onion seasoning that is applied to crisps. The model cheese and onion flavour developed in this study contained aroma compounds with a wide range of physio-chemical properties. The aim was to investigate the impact on aroma release from five different exemplar bases with varying chemical compositions: corn starch, wheat starch, corn flour, wheat flour, and maltodextrin using GC-Olfactometry, and SPME GC-MS. Seasoning powders were further evaluated using scanning electron microscopy to explain the impact of particle size on the flavour release. Corn flour had the maximum particle size with 650 µm and corn starch had the least (38 µm). maltodextrin (particle size of 95 µm) was the most successful flavour carrier with improved flavour release and a flavour profile containing 17 compounds. Wheat flour was the least improved flavour carrier with the weakest flavour profile. There were some compound specific effects, for example wheat flour retained higher levels of butanoic acid and benzyl alcohol. This study has scope for application across the food industry.